2000
DOI: 10.1073/pnas.97.7.3666
|View full text |Cite
|
Sign up to set email alerts
|

Direct interaction between synaptotagmin and the intracellular loop I-II of neuronal voltage-sensitive sodium channels

Abstract: Synaptotagmin, a synaptic vesicle protein involved in Ca 2؉ -regulated exocytosis, displayed direct high affinity interaction with neuronal sodium channels. Monoclonal antibodies directed against synaptotagmins I and II adsorbed in a concentration-dependent and -specific manner [ 3 H]saxitoxin prelabeled sodium channels extracted with detergent from nerve endings. Conversely, co-immunoprecipitation of synaptotagmin was achieved by antibodies against sodium channel subunits. Consistent with the co-immunoprecipi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
1

Year Published

2000
2000
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 50 publications
1
31
1
Order By: Relevance
“…No significant differences in the amounts of Navb1, Navb2 or Navb4 subunits immunoprecipitating from WT and Fgf14 ¡/¡ with the maPanNav antibody were observed. Consistent with previous reports that Syt2 directly interacts with Nav a subunits, 25 there was no apparent difference in the amount of Syt2 that could be precipitated from WT versus Fgf14 ¡/¡ cerebellar lysates with the maPanNav antibody (Fig. 5B).…”
Section: Present In Wt and Fgf14supporting
confidence: 81%
See 1 more Smart Citation
“…No significant differences in the amounts of Navb1, Navb2 or Navb4 subunits immunoprecipitating from WT and Fgf14 ¡/¡ with the maPanNav antibody were observed. Consistent with previous reports that Syt2 directly interacts with Nav a subunits, 25 there was no apparent difference in the amount of Syt2 that could be precipitated from WT versus Fgf14 ¡/¡ cerebellar lysates with the maPanNav antibody (Fig. 5B).…”
Section: Present In Wt and Fgf14supporting
confidence: 81%
“…In addition to iFGF14, the Nav a subunits, Nav1.1, Nav1.2, Nav1.4, and Nav1.6, as well as several proteins previously shown to interact with Nav a subunits, including Navb1, Navb2, Navb4, calmodulin, synaptotagmin-2, ankyrin G, casein kinase II and 14.3.3, [22][23][24][25][26][27] were also identified ( Fig. 3 and Table 1).…”
Section: Identification Of Proteins Immunoprecipitating With Ifgf14mentioning
confidence: 99%
“…For example, Syt III may sense an increase in intracellular Ca 2ϩ due to influx of extracellular Ca 2ϩ , whereas Syt VII may be relevant when intracellular Ca 2ϩ elevation is induced by intracellular mobilization through inositol 1,4,5-trisphosphate receptors. It has been demonstrated that synaptotagmin directly interacts with N-type (49 -57) or P/Q-type (19,54,55) Ca 2ϩ channels in neurons and Lc-type Ca 2ϩ channels (20). Inositol 1,4,5-trisphosphate receptors are present in pancreatic ␤-cells; however, it is currently unclear whether they associate with synaptotagmin.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, the C-terminal polypeptide of rNa v 1.2 (brain type II) was shown to bind calmodulin, suggesting modulation of these channels by Ca 2ϩ (23), and the rNa v 1.2-L1 was shown to interact with synaptotagmin in a Ca 2ϩ -regulated manner (46). An interaction with synaptotagmin may modulate sodium channel activity by controlling the accessibility of a protein kinase A phosphorylation site located inside the binding region of this complex or may play a role in the internalization of sodium channels (46). A more intriguing possibility is that this interaction may result in Na ϩ -dependent exocytosis (46).…”
Section: Discussionmentioning
confidence: 99%
“…An interaction with synaptotagmin may modulate sodium channel activity by controlling the accessibility of a protein kinase A phosphorylation site located inside the binding region of this complex or may play a role in the internalization of sodium channels (46). A more intriguing possibility is that this interaction may result in Na ϩ -dependent exocytosis (46). The TTX-R sodium channel rNa v 1.9a is preferentially expressed in small diameter C-type sensory neurons of DRG and trigeminal ganglia (14).…”
Section: Discussionmentioning
confidence: 99%